The F420H2 Dehydrogenase fromMethanosarcina mazei Is a Redox-driven Proton Pump Closely Related to NADH Dehydrogenases - Sebastian Bäumer; Tina Ide; Carsten Jacobi; André Johann; Gerhard Gottschalk; Uwe Deppenmeier (2000)
The F(420)H(2) dehydrogenase is part of the energy conserving electron transport system of the methanogenic archaeon Methanosarcina mazei Gö1. Here it is shown that cofactor F(420)H(2)-dependent reduction of 2-hydroxyphenazine as catalyzed by the membrane-bound enzyme is coupled to proton translocation across the cytoplasmic membrane, exhibiting a stoichiometry of 0.9 H(+) translocated per two electrons transferred. The electrochemical proton gradient thereby generated was shown to drive ATP synthesis from ADP + P(i). The gene cluster encoding the F(420)H(2) dehydrogenase of M. mazei Gö1 comprises 12 genes that are referred to as fpoA, B, C, D, H, I, J, K, L, M, N, and O. Analysis of the deduced amino acid sequences revealed that the enzyme is closely related to proton translocating NADH dehydrogenases of respiratory chains from bacteria (NDH-1) and eukarya (complex I). Like the NADH-dependent enzymes, the F(420)H(2) dehydrogenase is composed of three subcomplexes. The gene products FpoA, H, J, K, L, M, and N are highly hydrophobic and are homologous to subunits that form the membrane integral module of NDH-1. FpoB, C, D, and I have their counterparts in the amphipathic membrane-associated module of NDH-1. Homologues to the hydrophilic NADH-oxidizing input module are not present in M. mazei Gö1. Instead, the gene product FpoF may be responsible for F(420)H(2) oxidation and may function as the electron input part. Thus, the F(420)H(2) dehydrogenase from M. mazei Gö1 resembles eukaryotic and bacterial proton translocating NADH dehydrogenases in many ways. The enzyme from the methanogenic archaeon functions as a NDH-1/complex I homologue and is equipped with an alternative electron input unit for the oxidation of reduced cofactor F(420) and a modified output module adopted to the reduction of methanophenazine.